The evolution of the PO.DAAC: Seasat to SWOT. Issue 2 (15th July 2021) - Hausman, Jessica; Moroni, David; Gangl, Michael; Zlotnicki, Victor; Vazquez-Cuervo, Jorge; Armstrong, Edward M.; Oaida, Catalina; Gierach, Michelle; Finch, Christopher; Schroeder, Colleen
Abstract: The Physical Oceanography Distributed Active Archive Center (PO.DAAC) has been distributing satellite oceanographic data, including altimetry data, since the early 1980s. While it started by mailing magnetic storage tapes, PO.DAAC now distributes terabytes of data accessible within seconds, which will exponentially increase with future missions, such as the Surface Water and Ocean Topography (SWOT) mission. This paper will describe (1) the history of data accessibility through Pilot Ocean Data System (PODS) and the Seasat oceanographic satellite mission, (2) the present data accessibility and technological advances of PO.DAAC distributing data for TOPEX/Poseidon, the Jason series, and many other oceanographic missions through various tools and services and (3) the future paradigm of cloud services at PO.DAAC, ushered in by the large data volumes of the SWOT mission.